2023
DOI: 10.5194/nhess-23-733-2023
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary agent-based evacuation model: integrating the natural environment, built environment, and social system for community preparedness and resilience

Abstract: Abstract. Previous tsunami evacuation simulations have mostly been based on arbitrary assumptions or inputs adapted from non-emergency situations, but a few studies have used empirical behavior data. This study bridges this gap by integrating empirical decision data from surveys on local evacuation expectations and evacuation drills into an agent-based model of evacuation behavior for two Cascadia subduction zone (CSZ) communities that would be inundated within 20–40 min after a CSZ earthquake. The model also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…With the agent-based evacuation model, we found that urban structures reinforce attitudes towards tsunami evacuation and largely affect the success of evacuation. Unlike the conventional tsunami evacuation models 38 42 that have simplified decision-making processes including communications among evacuees, the model employed in this study can simulate comprehensive evacuation processes from decision-making with communications to detailed physical evacuation movements. This feature enables us to investigate the evacuation behaviours from attitudes towards evacuation.…”
Section: Discussionmentioning
confidence: 99%
“…With the agent-based evacuation model, we found that urban structures reinforce attitudes towards tsunami evacuation and largely affect the success of evacuation. Unlike the conventional tsunami evacuation models 38 42 that have simplified decision-making processes including communications among evacuees, the model employed in this study can simulate comprehensive evacuation processes from decision-making with communications to detailed physical evacuation movements. This feature enables us to investigate the evacuation behaviours from attitudes towards evacuation.…”
Section: Discussionmentioning
confidence: 99%
“…Social ecology theory is a theory that understands and explains human social behaviour and social systems from an ecological perspective [ 67 ]. It emphasizes the interrelationships and interactions between social systems and the natural environment, viewing society and the environment as an interdependent ecosystem [ 68 , 69 ]. The core ideas of the theory include the following.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Water 2023, 15, x FOR PEER REVIEW 3 of 20 stakeholders involved in hazard identification and warning issuance [46], the mechanisms of warning dissemination and their influence [47,48], as well as the preparedness and prior knowledge of the population regarding mobilisation and evacuation to safe places [49,50]. The spatial and temporal sectorisation of alerts and evacuations adapting the system to the specific characteristics of each sector can bring significant benefits in terms of system efficiency [51][52][53].…”
Section: Case Studymentioning
confidence: 99%
“…During the development process, the developed team encountered challenges in identifying and characterising an intermediate flood zone. To address this, they conducted a comprehensive review and expansion of the existing database compiled from the studies conducted by McClelland and Bowles [49] and Aboelata et al [50]. Nevertheless, specific issues identified in the 2.0 version were reported to the Risk Management Center of the U.S. Army Corps of Engineers.…”
Section: Sectorisation Scenarios and Lol Estimationmentioning
confidence: 99%
See 1 more Smart Citation